RBS and ERDA determinations of depth distributions of high-dose carbon ions implanted in silicon for silicon-carbide synthesis study - S. Intarasiri (2018)
For ion beam synthesis of silicon carbide (SiC), a knowledge of the depth distribution of implanted carbon ions in silicon is crucial for successful development. Based on its simplicity and availability, we selected Rutherford backscattering spectrometry (RBS) as an analysis technique for this purpose. A self-developed computer program dedicated to extract depth profiles of lighter impurities in heavier matrix is established. For control, calculated results are compared with an other ion beam analysis (IBA) technique superior for studying lighter impurity in heavier substrate i.e. elastic recoil detection analysis (ERDA). The RBS was performed with a 1.7-MV Tandetron accelerator using He2+as the probe ions. The ERDA was performed with a 5-MV Pelletron accelerator using I8+as the probe ions. This work shows that the RBS-extracted data had no significant deviations from those of ERDA and simulations by SRIM2003 and SIIMPL computer codes. We also found that annealing at temperatures as high as 1000 °C had quite limited effect on the redistribution of carbon in silicon. © 2006 Elsevier B.V. All rights reserved.